ChemInform Abstract: Two New Sesquiterpenoids from the Rhizomes of Curcuma xanthorrhiza. Issue 12 (March 2015) - Zhang, Chun‐Mei; Fan, Pei‐Hong; Li, Min; Lou, Hong‐Xiang
Abstract isolation and structure elucidation of two new sesquiterpenoids, zedoaridol (I) and bisaboladiene derivative (II), together with six known compounds